"They Will Take the Country from Us": Labor Zionism, the Origins and Legacy of the "Other" in Israeli Mass Media, and Hegemonic Narratives. (May 2014) - Frantzman, Seth J.
Abstract After 1948, Israel's governing elites embarked on a rigorous program of state building and settling hundreds of thousands of Jewish immigrants. In the process, the elites, primarily from the leading Mapai party, developed a process of othering Jewish immigrants from Arab countries, Arab citizens, and Orthodox Jews. They were physically segregated in their own schools and communities, and the elite culture described them as a threat against the European culture of Jewish immigrants from central Europe. The process targeted Mizrahi Jews before moving on to deplore the "demographic threat" of Orthodox Jews and resulted in the current normative hegemonic discourse in Israel that paints numerous groups as threatening the state. This article proposes a four‐part model for understanding "the other" in Israel: contemporary denial and nostalgia for a homogenous past, the view of Zionism as a civilizing mission, the application of separation of ethnic groups in planning, and demographic fear of the other. Altogether, they paint a picture of an Israel that has not come to grips with its past, and therefore continues the process of "othering" in its contemporary ethnocratic framework. Combining the analysis of geographic separation, and planning and media, it presents an innovative understanding of Israeli society.